Studying The Effect Of Radiation Therapy On Leucocytes In Cancer Patients With Diabetes Before, During And After Radiation Therapy (The Review of Diabetic Studies, 2025)
Background: Ionizing radiation is a standard treatment for brain tumors, but it may cause hematological changes, including leukopenia, anemia, and thrombocytopenia. Patients with chronic diseases such as diabetes may have altered responses during radiotherapy.Objective: This study aimed to evaluate the effect of radiotherapy on white blood cell (WBC) counts in brain tumor patients with and without diabetes, assessed before, during, and after treatment.Methods: A total of 50 patients with brain tumors (25 males, 25 females; mean age 42.6 years) were treated with Volumetric Modulated Arc Therapy (VMAT) using the TrueBeam 3.0 system at Al-Amal Hospital, Baghdad. Blood samples were collected at three stages: pre-, during, and post-radiotherapy. Patients who received chemotherapy or immunosuppressive drugs were excluded. WBC counts were analyzed in relation to age, tumor grade, and diabetic status.Results: Significant variations in WBC counts were observed across treatment stages according to age (p < 0.05) and tumor grade (p < 0.05). Grade 4 tumors (36%) and patients aged 25–59 years (38%) were the most affected groups. In contrast, no significant association was found between diabetes status and WBC counts during radiotherapy (p > 0.05).Conclusion: Radiotherapy significantly impacts WBC levels in brain tumor patients, with effects influenced by age and tumor grade, but not by diabetic status. Continuous hematologic monitoring is essential for optimizing patient management during treatment.